Aspectos da reprodução no gênero Characidium Reinhardt, 1867 (Crenuchidae, Characidiinae), na microbacia do Ribeirão Grande, serra da Mantiqueira, sudeste do Brasil - De Souza Braga, Francisco Manoel [UNESP] (Universidade Estadual de Maringa, 2006)
Aspects of the reproductive biology of Charaddium lauroi and C. alipioi were described. Maturation of the gonads was divided into four stages, and the distribution of the stages in an annual cycle was reported. The Charaddium lauroi has a higher spawning period in the spring, and the C. alipioi, in the summer. The size at sexual maturity of the Charaddium lauroi was about 4.2 cm total length for males and 5.1 cm for females; as for the C. alipioi, males were about 6.2 cm total length and females were about 5.8 cm. The gonadosomatic index values indicated the stage of maturity and were determined for each species and sex. The high values observed in October for Characidium lauroi males and females mark the maturation peaks in both sexes, and the peaks coincided with the spawning period. As for C. alipioi, the peaks were in February and also coincided with the spawning period.
Reproduction aspects of the genus Characidium Reinhardt, 1867 (Crenuchidae, Characidiinae) in the Ribeirão Grande system, serra da Mantiqueira, southeastern Brazil
Keywords: Characidium lauroi; Charaddium alipioi; Gonadosomatic index; Reproduction; animal experiment; Brazil; controlled study; female; fish; genus; gonad; male; nonhuman; sexual maturation; spawning; spring; summer; Characidiinae; Characidium; Crenuchidae